Quantitative parsimony: probably for the better - Jansson, Lina; Tallant, Jonathan (Oxford University Press, 2016)
Our aim in this article is to offer a new justification for preferring theories that are more quantitatively parsimonious than their rivals. We discuss cases where it seems clear that those involved opted for more quantitatively parsimonious theories. We extend previous work on quantitative parsimony by offering an independent probabilistic justification for preferring the more quantitatively parsimonious theories in particular episodes of theory choice. Our strategy allows us to avoid worries that other considerations, such as pragmatic factors of computational tractability and so on, could be the driving ones in the historical cases under consideration.